Dairy products from Cariri Paraíba and their impacts on the environment (Research, Society and Development, 2022)
The objective of this work was to detect the current methods of waste management used in dairy products in Cariri, Paraíba. An environmental diagnosis of the dairy was carried out. All production lines were monitored and aspects such as the manufacturing process, waste generated, cleaning procedures and process failures that could generate environmental impacts were observed. Technical visits were made during the month of May 2020, to carry out the diagnosis and application of the questionnaire. Of the analyzed dairy products, five are small and two are medium. The use of the whey is partial and consists of the manufacture of ricotta and its disposal for animal feed. Four dairy is small per and has no ETE. The five dairies are located in the countryside. Despite being small, the studied dairy industry generates residues which are released into the environment without treatment. For the dairy to adapt to the sustainable production process, it is necessary to implement some mitigating measures. Through the study it is noted that several proposed measures do not require high investments and technology just some changes and attitude.